Organ and tissue donation for transplants: experiences during the COVID-19 pandemic (Research, Society and Development, 2022)
The study sought to investigate the experiences of professionals who work with the process of organ and tissue donation for transplants during the COVID-19. This is a qualitative study that, using the Snowball Sampling Technique, interviewed participants from three states in the Northeast of Brazil. As results, it was found that the report of death to family members and the adequacy of service routines after the New Coronavirus pandemic are situations considered difficult to manage by professionals. The insufficiency of knowledge about the donation process and the lack of structure are mentioned as obstacles; and feelings of both anguish and gratitude stand out in the routine of teams in the three states. It was concluded that reporting bad news in the donation process is a relevant issue that needs to be debated in order to rethink the training of professionals in the field of health. The study confirms that there are multiple factors that underlie the decision-making of families, but that the quality of the reception given, the safety and preparation of the interviewer, especially adequate communication, are fundamental for an outcome in favor of the donation.